Pengembangan Media Flashcard Pada Pembelajaran IPA Materi Perpindahan Panas Kelas V Sekolah Dasar Kota Semarang - Dwi Suratimah; Sumarno Sumarno; Ida Dwijayanti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The purpose of this research is to produce a development product, namely learning Flashcard media with heat-insulating materials presented in the form of pictures and writing. Methods Data collection instruments used were observation, interviews, and documentation. the design of the development of Flashcard learning media on the hottest material can attract attention and generate interest in learning for fifth grade elementary school students in Banyumanik District, Semarang City. The eligibility of the media was also obtained from the educator's response to the Flashcard learning media on the heat locking material developed by the researcher. A score of 98% was stated in the very feasible category, which means that this Flashcard learning media received positive responses because the media can attract attention and increase interest in learning. student.